Caminhos da professoralidade no Curso de Dança da UFU: impasses e desafios na construção da identidade profissional - Nunes, Dalma Persia Nelly Alves (2016)
Teacher identity is a subject of study and discussion in the academic world whichhas become an object of attention of researchaddressing teaching and teacher formation. Life history, initial and continuing formation, the meaning of teaching to the teacher, and also pedagogical practice are all contributing factors to teachers’ professional identity. The present study is a proposal developed in the research field of Educational Knowledge and Practice, and its main focus lies in university teaching. Higher education teaching in the context of a dance course, and the issues and challenges of constructing teachers’ professional identity are presented. Thus, my main questions were: what is the teaching path followed by newly hired dance teachers in the Federal University of Uberlândia? How is teaching identity developed in these new teachers’ professional socialization process? What kind of educational knowledge is (re)produced and mobilized by teachers when they join university teaching? In order to answer these questions, my objectives are: to analyze the teaching path of the newly hired dance teachers of the Federal University of Uberlândia; to investigate how their teaching identity is built within their professional socialization process; and identify the kinds of educational knowledge they (re)produce and mobilize as soon as they become university teachers. The present research comprises a qualitative data analysis from previous studies on the subject, having as starting point relevant bibliographic research, followed by an identification questionnaire and an interview conducted with the newly hired dance teachers. The construction of teaching identity is related to objective and subjective conditions involving a teaching job and how the teacher perceives this identity as constantly evolving. Hence I understand the importance of personal and institutional incentives to prepare studies which raise or problematize issues specific to this area, contributing to extend the debate over higher education professionals’ formation, in particular that of dance course teachers on national scope.